Public-Private Partnership in Agribusiness - Akimova, Yulia Alekseevna; Kochetkova, Svetlana Andreevna; Kovalenko, Elena Georgievna; Zinina, Lubov Ivanovna (International Review of Management and Marketing, 2016)
Reformation of the country’s agribusiness fundamentally changes the approach to establishing the competitive enterprises in the agrarian sector, which is so far the problem of realization of the agrarian policy in conditions of ensuring economic and food security of the country. State aid to agriculture leads to increased competitiveness of the sector, the emergence of additional resources that create the corresponding part of the demand for factors of production, increase the attractiveness of the sector for credit, investment and other institutions. The transition to innovative development and modernization of the economy provides an active search for tools to encourage innovation and investment activity of private funds, while ensuring the most effective balance of interests of the state and business structures. The mechanism of public-private partnership (PPP) is used as such a tool. The main objective of the research is to study the mechanism of realization of the state-private partnership in the Russian and foreign practice of development of the agrarian sector, as well to develop of priority directions of its improvement. The authors of the article substantiated the necessity of the use of new financial tools to ensure the innovative development of the agrarian sector, such as technology platforms, venture capital funds, agro-industrial parks and rental leasing relationship. Realization of these measures will contribute to the effective development of public-private partnership in the Russian agribusiness in the modern conditions of the unstable environment. Keywords: public-private partnership, agribusiness, agriculture, foreign experience, program, improvement. JEL Classifications: H54, H82, Q10